Does limited gear ratio driven higher training cadence in junior cycling reflect in maximum effort sprint? - Rannama, I.; Port, K.; Bazanov, B. (Journal of Human Sport & Exercise, 2012)
Maximum gears for youth category riders are limited. As a result, youth category riders are regularly compelled to ride in a high cadence regime. The aim of this study was to investigate if regular work at high cadence regime due to limited transmission in youth category riders reflects in effectual cadence at the point of maximal power generation during the 10 second sprint effort. 24 junior and youth national team cyclist`s average maximal peak power at various cadence regimes was registered on Cyclus-2 ergometer using cyclists own bikes. Effectual cadence at the point of maximal power generation (group average 113.9±10.6 rpm) is similar to the values of professional road cyclist during the last 200m sprinting to finish where 10 second average cadence is 109.9±5.3 rpm and highest average cadence is 117.6±6.1 rpm. The premise that regular work at high cadence regime due to limited transmission in youth category riders reflects in effectual cadence at the point of maximal power generation during the 10 second sprint effort was not corroborated.